1948
DOI: 10.1002/jctb.5000670405
|View full text |Cite
|
Sign up to set email alerts
|

The preparation of methylpyridines by catalytic methods

Abstract: The action of methyl alcohol on pyridine in the vapour phase in contact with alumina or aluminium silicates gives methylpyridines, including the commercially valuable β‐picoline. The separation of this base from the other homologues of similar boiling‐point can be effected by taking advantage of the fact that it does not condense with m‐nitrobenzaldehyde to form a stilbazole. Small yields only of β‐picoline are obtained by heating (a) ammonia and (b) urea with glycerol in the presence of the same catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

1960
1960
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…More than sixty years ago, Cullinane et al mentioned the formation of pyridine and derivatives by reacting ammonia, urea or ammonia salts with glycerol for about 10 hours, but the selectivity and yield of pyridine were too low to be applied in industry. 19 Acrolein is an important intermediate in the production of pyridines from formaldehyde and acetaldehyde. Many literature papers have reported that acrolein could be produced from glycerol via a catalytic gas phase dehydration process.…”
Section: Introductionmentioning
confidence: 99%
“…More than sixty years ago, Cullinane et al mentioned the formation of pyridine and derivatives by reacting ammonia, urea or ammonia salts with glycerol for about 10 hours, but the selectivity and yield of pyridine were too low to be applied in industry. 19 Acrolein is an important intermediate in the production of pyridines from formaldehyde and acetaldehyde. Many literature papers have reported that acrolein could be produced from glycerol via a catalytic gas phase dehydration process.…”
Section: Introductionmentioning
confidence: 99%
“…(mp 133°, lit.6 mp 134°) and Ie (mp 87°, lit.6 mp 85-87°) were prepared by the same procedure as used by de la Mare and co-workers. 5 Reaction of Aniline with .-A side-arm test tube, equipped with thermometer and nitrogen line, was charged with 15 ml of aniline and 2.70 g (10 mmoles) of . The tube was heated in an oil bath maintained at 110°.…”
Section: Nphmentioning
confidence: 99%
“…As the previous study showed, using glycerol as feedstock could form many aldehydes that are also the raw materials for the production of pyridines, such as acrolein, acetol, formaldehyde, and acetaldehyde. , Thus, it is possible to convert glycerol to synthesis pyridine. Cullinane et al reported the formation of pyridine rings by reacting ammonia with glycerol . Xu et al conducted several experiments to confirm the catalytic activity of HZSM-5, which is a one step process expanding the yield of pyridines, which exhibits an extraordinary application potential for using glycerol to synthesize pyridines. , It was suggested that the dehydration of glycerol, the amination of oxidation products, and the polymerization of imine substances occurred during the pyridine synthesis process.…”
Section: Introductionmentioning
confidence: 99%
“…Cullinane et al reported the formation of pyridine rings by reacting ammonia with glycerol. 30 Xu et al conducted several experiments to confirm the catalytic activity of HZSM-5, which is a one step process expanding the yield of pyridines, which exhibits an extraordinary application potential for using glycerol to synthesize pyridines. 31,32 It was suggested that the dehydration of glycerol, the amination of oxidation products, and the polymerization of imine substances occurred during the pyridine synthesis process.…”
Section: ■ Introductionmentioning
confidence: 99%